2006
DOI: 10.1159/000095001
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Profile of Spanish-Catalan Children with Specific Language Impairment at Age 4: Are There Any Changes over Time?

Abstract: The phonology of a group of Spanish-Catalan children with specific language impairment (SLI, n = 5), who had been analysed at age 3;10, is now analysed at age 4;09 and compared with two control groups: an age-matched control (n = 5) and a language level control (measured using the mean length of utterance by words; n = 5). The children with SLI continue to show a delay in the acquisition of segments, syllabic structures and in the use of the simplification processes, but not in word structures, compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 32 publications
0
6
0
2
Order By: Relevance
“…Because of the high correlations attested cross-linguistically between MLU measured in morphemes and MLU measured in words (Parker & Brorson, 2005), MLUw has been typically used to make comparisons between languages with different degrees of morphological complexity (Anderson, 1999). Aguilar-Mediavilla and Serra-Raventos (2006), who compared the speech sound production of five Spanish-Catalan bilingual 4-year-olds with language impairment to two typically-developing control groups, one matched on age and the other on proficiency (based on MLUw), found that children with greater MLUw had more advanced segmental abilities in Spanish than those with poorer language skills.…”
Section: Relationships Between Phonological Skillsmentioning
confidence: 99%
“…Because of the high correlations attested cross-linguistically between MLU measured in morphemes and MLU measured in words (Parker & Brorson, 2005), MLUw has been typically used to make comparisons between languages with different degrees of morphological complexity (Anderson, 1999). Aguilar-Mediavilla and Serra-Raventos (2006), who compared the speech sound production of five Spanish-Catalan bilingual 4-year-olds with language impairment to two typically-developing control groups, one matched on age and the other on proficiency (based on MLUw), found that children with greater MLUw had more advanced segmental abilities in Spanish than those with poorer language skills.…”
Section: Relationships Between Phonological Skillsmentioning
confidence: 99%
“…Os dados observados neste estudo, com relação à fonologia das crianças com AEL, corroboram achados da literatura (1,(8)(9)(10) .…”
Section: Discussionunclassified
“…O desenvolvimento fonológico das crianças com DEL caracteriza, na maioria dos casos, um distúrbio e não apenas um atraso; são observados atrasos na aquisição de nasais, vogais e plosivas, além de processos idiossincráticos como redução de sílabas átonas, omissão de consoantes iniciais e trocas de vogais (7,8) .…”
Section: Introductionunclassified
“…A study of PSP in Catalan and Spanish-speaking children between 3:0 and 4:0 years old with speciic language impairment (SLI) observed changes in their phonological proile [29]. The most signiicant PSP at 3 years old were syllable omissions, especially when compared against a control group of the same age.…”
Section: Phonological Problems In Spanish-speaking Childrenmentioning
confidence: 99%